THE IMPROVING STUDENTS’WRITING SKILL THROUGH CLUSTERING TECHNIQUE - megawati megawati (LPPM Universitas Mohammad Husni Thamrin, 2019)
Students four grade semester English Education Department have difficult in writing. They have limitation in English vocabulary building, students didn’t understand systematically in writing. They usual use common words in writing English so that they weak in writing skill. Lecturer choose clustering technique to improve students’writing skill. The advantages this technique can mapp students’mind, an idea or theme with symbols and diagram after that they can improve become written or text. Furthermore all of the content in which they want to write based on the outline. This research aim to know improving students’writing skill through clustering technique on students STKIP Kusuma Negara, Jakarta. It is qualitative research using classroom action research method. It was conducted two cycle. Each of cycle consist of four steps. There are planning, acting, observing and reflecting. This research was conducted with the subject twenty five students in fourth semester English Education STKIP Kusuma Negara Jakarta. Data were collected through interview, observation and test. The result of this research is improving students’writing skill through Clustering Technique showed an increasing percentage and average score. Cycle I was 32 % students pass in writing skill or the average score is 73.28, in Cycle II was 88 % students pass in writing skill or the average score is 81.6. The students given positive responses, they were enthusiastic and motivated when they written in English by Clustering Technique. Based on the result, it can be concluded Clustering Technique could improve the students’writing skill on STKIP Kusuma Negara.